1992
DOI: 10.1148/radiology.182.1.1727286
|View full text |Cite
|
Sign up to set email alerts
|

Bone signal abnormalities in the posterolateral tibia and lateral femoral condyle in complete tears of the anterior cruciate ligament: a specific sign?

Abstract: Thirty-two patients with acute, complete tears of the anterior cruciate ligament (ACL) proved at surgery underwent examination with magnetic resonance (MR) imaging. Bone impaction sites were present in the posterolateral tibial plateau in 30 patients (94%) and in the lateral femoral condyle (LFC) in 29 patients (91%). The bone abnormalities had low signal intensity on T1-weighted images and high signal intensity on T2-weighted images when compared with the signal intensity of normal marrow. It is assumed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(91 citation statements)
references
References 0 publications
7
82
1
1
Order By: Relevance
“…Vellet et al (1991) found that rotation of the tibia and femur relative to each other, as well as deceleration, and valgus force had occurred in two thirds of 83 patients with bone bruise injuries. Others think that the lesion is caused by traumas and forces similar to those which cause an anterior cruciate ligament rupture (Murphy et al 1992, Stallenberg et al 1993, Stein et al 1995, Zeiss et al 1995. During anterior translation, the posterior aspect of the lateral tibial plateau impinges on the lateral femoral condyle or else a violent reduction of a pivot-shift event might occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vellet et al (1991) found that rotation of the tibia and femur relative to each other, as well as deceleration, and valgus force had occurred in two thirds of 83 patients with bone bruise injuries. Others think that the lesion is caused by traumas and forces similar to those which cause an anterior cruciate ligament rupture (Murphy et al 1992, Stallenberg et al 1993, Stein et al 1995, Zeiss et al 1995. During anterior translation, the posterior aspect of the lateral tibial plateau impinges on the lateral femoral condyle or else a violent reduction of a pivot-shift event might occur.…”
Section: Discussionmentioning
confidence: 99%
“…During anterior translation, the posterior aspect of the lateral tibial plateau impinges on the lateral femoral condyle or else a violent reduction of a pivot-shift event might occur. It has been suggested that, with the knee less flexed, the osseous contusion appears more anteriorly on the lateral femoral condyle, and moves posteriorly with increased flexion (Murphy et al 1992, Stein et al 1995. In our study, we could not determine the mechanism of injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow edema-like lesions (BMELs), which appear as patchy high signal abnormalities on fat-suppressed T 2 weighted MR images, are observed in on average 70% of patients with acute ACL injuries (7). During ACL rupture, the anterior lateral femur impacts on the posterior lateral tibia which leaves a "footprint" on the femur and tibia, also known as "kissing lesions" (8). The presence of BMELs was reported to correlate with meniscal tears, collateral ligament tears and large volumes of BMEL were associated with cortical fractures (7,9,10), suggesting BMEL as a potential indicator of injury severity.…”
Section: Introductionmentioning
confidence: 99%
“…1 These BBs are most common in the lateral tibiofemoral compartment. 2 Whereas the clinical importance of these BBs remains unclear, they have been shown to increase symptoms 3 and disability [3][4][5] after injury. Specifically, Johnson et al 3 demonstrated that, compared with individuals with an isolated ACL injury, patients with lateral BBs had larger and longer-lasting knee-joint effusions, increased pain, prolonged restoration of normal knee range of motion, and delayed return of nonantalgic gait without the use of assistive devices.…”
mentioning
confidence: 99%